The Effect of Aromatherapy with Lavender Essence on Depression and Headache Disability in Migraine Patients: A Randomized Clinical Trial - A Jafari-Koulaee; F Khenarinezhad; A Sharifi Razavi; M Bagheri-Nesami (Institue of Medicinal Plants, ACECR, 2019)
Background: Disability due to headache in migraine and being chronic of it can lead to sadness and depression. Objective: This study was aimed to determine the effect of lavender aromatherapy on depression and headache disability. Methods: This clinical trial study was conducted on 60 migraine patients referred to Toba Clinic of Sari (Mazandaran, Iran) during 2016-2017. Patients in the experimental group inhaled 2-3 drops of lavender essence for 15 min, three times a week for 4 consecutive weeks. The dose, duration and inhalation method of paraffin (as placebo) in control group were similar to those in the experimental group. Before the intervention, at the end of the second and fourth weeks, the intensity of depression and headache disability were measured by Beck Depression Inventory (BDI-13) and Jacobson questionnaire. For analyzing in each group and groups, repeated measure tests and Boneforeni were used. Results: In experimental group, depression (P <0.001, F=64.49) and headache disability scores (P <0.001, F=29.95) were significantly different in the pre intervention, two and four weeks after the intervention. No statistically significant differences were observed between the two groups in terms of the depression (P = 0.13, f = 2.6) and headache disability (P = 0.15, f = 1.93) scores before, two and four weeks after intervention. Conclusion: Lavender essential oil can be useful for reducing depression and headache disability in migraine patients.